PERAN BUDAYA LOKAL DALAM PELESTARIAN NILAI - NILAI PANCASILA DI ERA MODERN DI KOTA TERNATE - Muin, Djono; Djaohar, Sulaiman (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
Local wisdom consists of tangible local wisdom in the form of rules/value systems, building architecture, traditional tools and weapons and intangible such as advice/proverbs, songs, rhymes, and folk tales. The loss of local culture in Indonesia is a serious concern along with the rapid development of technology and the flow of global information. Technological advances allow people, especially the younger generation, to be easily exposed to foreign cultures through social media platforms, films, and music. This design uses a type/research approach in the form of Library Research. Library study is a study used in collecting information and data with the help of various materials available in libraries such as documents, books, magazines, historical stories. This study shows that Pancasila has a close relationship with local culture. As Indonesian citizens, we must preserve local culture in Ternate City through various means and facilities, because local wisdom in Ternate City has behaviors, procedures, and values ​​contained therein to uphold togetherness in various dynamics of community life so that attitudes of tolerance, mutual cooperation can be developed in accordance with the characteristics of local wisdom.